Carbon Border Adjustment Mechanism: from a green vision to fading alignment with the WTO and EVFTA: bridging divergences between the EU and developing countries - Anh Nguyen Thi Kim; Hy Nguyen Hoang Thai; Hien Nguyen Xuan My (TalTech Journal of European Studies, 2025)
The Carbon Border Adjustment Mechanism (CBAM) of the European Union (EU) is considered one of the pivotal pillars of the European Green Deal, with the aim of reducing carbon leakage and promoting sustainable development. However, the CBAM, with other unilateral initiatives under the EGD framework, including ‘Renewables Energy Directive Recast’ to 2023 (RED II) and ‘European Regulation on deforestation-free products’, received various negative reactions from EU partners globally, particularly in Southeast Asia. Indonesia and Malaysia, two significant exporters of palm oil to the EU, have initiated claims against the EU’s RED II under the World Trade Organization’s (WTO) dispute settlement mechanism. In this context, the EU’s response to concurrent criticism and disputes within the WTO framework demonstrates clear and consistent strategies aimed at establishing itself as a leader in sustainable development in both global and transcontinental regional trade.